Dynamic Effects in Asynchronous Circuits - Deeg, Florian; Sattler, Sebastian (GMM-Fachberichte, 2022)
The aim of this paper is to summarize the dynamic effects of asynchronous circuits again and to verify them using logical models and real basic examples. The effects of hazards and races are presented theoretically and formally, and a new formula for recognizing races is derived from this. Examples of how these formulas can be applied are then shown. The effects are made visible with the help of a specially developed circuit board and an oscilloscope.
CRIS-Team Scopus Importer:2024-12-16